2022
DOI: 10.1038/s41598-022-17945-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of abbreviated protocols versus unenhanced MRI in detecting occult breast lesions of mammography in patients with dense breasts

Abstract: To assess the diagnostic ability of abbreviated protocols of MRI (AP-MRI) compared with unenhanced MRI (UE-MRI) in mammographically occult cancers in patients with dense breast tissue. The retrospective analysis consisted of 102 patients without positive findings on mammography who received preoperative MRI full diagnostic protocols (FDP) between January 2015 and December 2018. Two breast radiologists read the UE, AP, and FDP. The interpretation times were recorded. The comparisons of the sensitivity, specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In the current systematic review, three of seven the studies followed the negative cases for two years (6,16,17). Three of the studies followed for less than two years(7, 9, 10) and one study did not state the follow-up time(8).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the current systematic review, three of seven the studies followed the negative cases for two years (6,16,17). Three of the studies followed for less than two years(7, 9, 10) and one study did not state the follow-up time(8).…”
Section: Discussionmentioning
confidence: 85%
“…We found that the total acquisition time and reading time for ABB-MRI (AP protocol) is by farm shorter than previously known full protocol MRI. In the AP protocol, the time to perform ranges between 3-20 minutes (9,17) which are shorter than 20-45 minutes in full protocol breast MRI (19). The reading time for ABB-MRI ranges between 28-54 seconds(6, 16) compared to the previous reports on full protocol which is 6.43 minutes(3).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…153 Detection performance between unenhanced DWI, T1W, T2W, AB-MRI and full MRI protocols has also been compared demonstrating almost equivalent performance. 154,155 Although DWI as a stand-alone technique has demonstrated high performance, its sensitivity is still inferior to that of DCE-MRI (Fig. 7).…”
Section: Mri Techniquesmentioning
confidence: 99%
“…Likewise, due to the limited spatial resolution of DWI, small lesions (<10 mm) are not easily detectable, thus increasing the false-negatives. 155 This is of utmost importance, as many lesions may not be detected as early as with DCE-MRI and/or AB-MRI when performing only Research has focused on developing more robust DWI acquisition strategies such as readout segmented echo planar imaging (rsEPI) and reduced field-of-view (rFOV), as well as advanced reconstruction and postprocessing (correction and optimization) algorithms, to improve spatial resolution, image quality, and reduce artifacts. 150,152 In parallel, efforts to standardize DWI acquisition parameters and interpretation have recently been suggested for lesion classification.…”
Section: Mri Techniquesmentioning
confidence: 99%